2019
DOI: 10.21608/aprh.2019.14036.1085
|View full text |Cite
|
Sign up to set email alerts
|

Validated HPLC Determination of the Potential Anti-Helicobacter pylori, Lepidine, in Lepidium sativum Seeds Assessed by Molecular Docking Study

Abstract: Background: Nearly 50 % of the world residents are known to be infected with Helicobacter pylori which is the main cause of peptic ulcer and gastric cancer. Since resistance to the currently used treatments, other alternative approaches such as combination with natural products should be tried. Objectives: In this work, validated HPLC-UV method was developed for quantification of lepidine content in various extracts and crude oil of Lepidium sativum seeds. Furthermore, antibacterial activity of lepidine agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Broth microdilution was performed with 96-well U-shaped bottom microtiter plates following Clinical and Laboratory Standards Institute (CLSI) guidelines (2017). 38,39 …”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broth microdilution was performed with 96-well U-shaped bottom microtiter plates following Clinical and Laboratory Standards Institute (CLSI) guidelines (2017). 38,39 …”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Broth microdilution was performed with 96-well Ushaped bottom microtiter plates following Clinical and Laboratory Standards Institute (CLSI) guidelines (2017). 38,39 The tested samples were used in an initial concentration of 100 mg mL À1 and then serially diluted two-fold to obtain concentrations in the range of 0.098-50 mg mL À1 . The inoculum of H. pylori was prepared in Columbia broth, with the OD 600 nm adjusted to 0.5.…”
Section: Preparation Of the Most Effective Mentha Extract Polymeric Mmentioning
confidence: 99%
“…The obtained results indicated that satisfactory accuracy and precision were obtained as the values of RSD did not exceed 2%, with additional mean recoveries within the range of 98–102%. 38 , 39 The method’s robustness was estimated by investigating the deliberate change of flow rate and acetonitrile percentile by 0.2 units. The mentioned changes did not remarkably affect the results, indicating the satisfactory performance of the method for implementation in different laboratories.…”
Section: Resultsmentioning
confidence: 99%